2017
DOI: 10.1016/j.apal.2017.02.003
|View full text |Cite
|
Sign up to set email alerts
|

On the decidability of the theory of modules over the ring of algebraic integers

Abstract: Abstract. We will prove that the theory of all modules over the ring of algebraic integers is decidable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 16 publications
(40 reference statements)
0
12
0
Order By: Relevance
“…The decidability of the theory of modules over the ring of algebraic integers Z has also been obtained by S. L'Innocente, G. Puninski and C. Toffalori, using different methods [19]. 6.2.…”
Section: Applicationsmentioning
confidence: 96%
“…The decidability of the theory of modules over the ring of algebraic integers Z has also been obtained by S. L'Innocente, G. Puninski and C. Toffalori, using different methods [19]. 6.2.…”
Section: Applicationsmentioning
confidence: 96%
“…Each B P is a valuation domain, and the Ziegler spectrum of this class of rings was thoroughly investigated (see [17, Chapters 12,13], or [6] for recent development). In more detail, let Γ denote the value group of a valuation domain V .…”
Section: Weakly Prime Idealsmentioning
confidence: 99%
“…However, as it was mentioned there, this information is expected to be elaborated for particular classes of Bezout domains. One example of this refinement was given in [22], and some information on the structure of the Ziegler spectrum of the ring of algebraic integers is contained in a recent preprint [16].…”
Section: Introductionmentioning
confidence: 99%
“…Proof. By [10,Lemma 3.3] (using the Krull dimension 1 hypothesis) the prime radical relation a ∈ rad(bR) can be decided effectively for a, b ∈ R.…”
Section: N) Are Pairwise Comparable Under Inclusionmentioning
confidence: 99%
“…The theory of modules of Bézout domains of the form D + XQ[X] ⊆ Q[X], where D is a principal ideal domain with field of fractions Q, is shown in [PT14] to be decidable under certain reasonable effective conditions on D. In particular, it is shown that Z + XQ[X] has decidable theory of modules. The theory of modules of the ring of algebraic integers, along with some other Bézout domains with Krull dimension 1, is shown to have decidable theory of modules in [LTP17].…”
Section: Introductionmentioning
confidence: 99%